Prawo kanonizacyjne w rozwoju historycznym - Lis, Artur (Przegląd Prawno-Ekonomiczny, 2015)
Streszczenie dostępne wyłącznie w języku angielskim: From the very beginning of the Church’s history the saints were worshiped in the public cult. It deadline the canonization the moral perfection - was defined was as official acknowledgement through Apostolic Capital of holiness of life concrete human person with right of achievement by her in heroic degree or the devotion his lives for Christ, depending on acknowledgement her by pope for stately person of public cult in general Church the and inscription to catalogue of saints. The canonization concerns the life of moral Church, saint he be worshiped not only, as this, who with whole certainty be saved but also, as stately the imitation the example of Christian life (the ecclesial value of canonization process). Former matters were an important issue in the canonization proceeding. These matters are especially significant when the evidences concerning the virtues, especially those of God’s servant martyrdom, are strictly based on the written sources and when there is a lack of the eye-witnesses who can confirm heroism of virtues or God’s servant martyrdom. In this article, the analysis of historical and legal matters will be subject to the procedure of old (historical).